Moving to Advanced Research on Human Machine Interface Design - Keith Brawner (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
This poster paper will discuss a variety of items related to Human-Machine Teaming and research in support in-creasing control of autonomous machines present in phys-ical problem domains of interest.  Many military tasks can be decomposed into their primary elements – intelligence preparation, reconnaissance, movement, maneuver, fires, and and support across the combat domains of interest – air, land, sea, etc.  There are an increasing number of au-tonomous and semi-autonomous ground-based systems available, such as the Multi-Utility Tactical Transport (MUTT) Unmanned Ground Vehicle, for movement of materials, or Quadrupedal Unmanned Ground Vehicle (QUGV) for the disposal of explosive ordinance, comple-mented by aerial platforms considering of a wide variety of Unmanned Aerial Systems (UAS) for the gathering and transmitting of information, held together by a common backbone and network.